LIMN LOGICAL STUDIES OF GHURDAUR POND HAJIPUR - PRADMASNA KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
The aquatic habitats situated in Maya Sarovar (Bodh-Gaya pond) are some of the most sensitive indicators of environmental change Their normal elevation leads to increased exposure to ultraviolet radiation as well as a shortened growing season that aggravates plankton populations due to Maya Sarovar temperature and light limitations In order to assess the various limnological characteristics of Maya Sarovar (Bodhgaya Pond), their physico-chemical and analysis was carried out. Study of planktonic population in relation to water chemistry provides the basic information of entire ecology of the pond. Plankton are considered indicators of the different trophic status of a water body because of their specific qualitative features and their capacity to reproduce in large number under environmental conditions that are favourable to them[3] and they used for pollution surveillance Plankton are important part of aquatic life and good indicator of changes in water quality because they are strongly affected by environmental conditions and responds quickly to changes in environmental quality. Apart from primary production, Limnology play an important role as food for herbivorous animals and act as biological indicators of water quality in pollution studies while, zooplankton occupy a vital role in the trophic structure of an aquatic ecosystem and play a key role in the energy transfer. Hence qualitative and quantitative assessments of plankton are of great importance.